COMPARATIVE EVALUATION OF CASTOR (RICINUS COMMUNIS) AND PONGAMIA (PONGAMIA PINNATA) LEAF POWDERS FOR ECO-FRIENDLY SUPPRESSION OF PLANT PARASITIC NEMATODES (MELOIDOGYNE SPP.) IN OKRA (ABELMOSCHUS ESCULENTUS L. MOENCH) - Kumshe, Isa Bukar; Mohammed, Fatima Kubili; Bukar, Ahmadu; Muastapha, Muhammad (FUDMA JOURNAL OF SCIENCES, 2025)
Root-knot nematodes (Meloidogyne spp.) are major soil-borne pests that reduce okra yield and profitability in tropical and subtropical regions. Concerns over the environmental safety of synthetic nematicides have led to increased interest in botanicals. This study compared the nematicidal performance of Castor (Ricinus communis) and Pongamia (Pongamia pinnata) leaf powders at 10 g per treatment under field conditions in Nigeria. A randomized split-plot design was used with Carbofuran as a standard chemical control. Castor leaf powder at (10 g) per treatment significantly reduced nematode populations and improved plant growth and yield, performing on par with Carbofuran and better than pongamia. These findings reinforces the viability castor leaf powder (10 g) for nematode management in okra cultivation.